Introduction to the special section on predictors and outcomes of peer victimization - Garandeau, Claire; Malamut, Sarah; Laninga-Wijnen, Lydia (Sage, 2025)
The eight longitudinal studies published in this special section rely on data from five countries and on rigorous methodologies (such as genetically sensitive, multilevel, or experimental designs) to shed light on predictors and outcomes of peer victimization at school. This introduction highlights the main questions addressed by the current set of studies. First, we present studies which sought to identify the factors that a) put children and youth at higher risk of victimization by peers and b) exacerbate the effects of these vulnerability factors, as well as to determine whether genes account for some of these effects. Second, we present studies focusing on the links between peer victimization and later biological, psychological and social adjustment and on the possible moderators and mediators of these associations. Together, these studies help us better understand the maladaptive cycle of peer victimization, which can inform the development of school-based and targeted interventions.